A lady with lethargy. - Md Noor, Sabariah; George, Elizabeth; Idris, Faridah; Shariff Ghazali, Sazlina (Universiti Putra Malaysia Press, 2012)
An example of problem based approach of a lady with thalassaemia: a guide for medical student.